Coumarin-Encapsulated Solid Lipid Nanoparticles as an Effective Therapy against Methicillin-Resistant Staphylococcus aureus - Mohammed H. Alqarni; Ahmed I. Foudah; Aftab Alam; Mohammad A. Salkini; Magdy M. Muharram; Nikolaos E. Labrou; Pinki Rawat (Bioengineering, 2022)
Bacterial infections caused by antibiotic-resistant pathogens are a significant public health problem. This is because the transmission of infectious diseases is shifting, and new antibiotic-resistant strains of bacteria are emerging. The development of biofilms that are resistant to antibiotics poses another hurdle to drugs and treatment alternatives. Therefore, there is an urgent need to develop innovative strategies to effectively eliminate antibiotic-resistant microorganisms effectively. Natural coumarins have broad spectrum bioactivity and the potential for lower resistance. Coumarin is a secondary metabolite found in certain plants, fungi, and bacteria. It is highly effective against methicillin-resistant Staphylococcus aureus (MRSA). Therefore, coumarin can be used as an alternative to combat MRSA. However, most antibacterial agents lack selective targeting of pathological sites, limiting the efficacy of their antibacterial activity. Efficient MRSA treatments can be achieved through nanoparticle (NPs)-based targeted therapies. To address this challenge, a novel coumarin-loaded solid lipid nanocarrier for MRSA was developed to overcome this challenge. The developed systems exhibited a particle size of 138.5 ± 76.06 nm and a polydispersity index (PDI) of 0.245 ± 0.00. The zeta potential of coumarin-loaded SLNs was reported to be −22.2 ± 8.15 mV with a spherical shape. The encapsulation efficiency of coumarin was reported to be 63.09 ± 3.46% in the final formulation. The developed formulation was biocompatible with a minimum inhibitory concentration (MIC) of 1.08 µg/mL. This study suggests that coumarin-loaded SLNs can effectively treat MRSA infections.